Exploring Vandergrift ‘s Metacognitive Strategies Use and Its Impact on Listening Comprehension: A Comprehensive Review - Syahfutra , Wandi; Safriyanti, Maria; Yusandra, Titiek Fujita (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
This article aimed to explore various metacognitive strategies use and its impact on listening comprehension based on five components or factors of Vandergrift’s metacognitive awareness listening questionnaire (MALQ) at different research areas. The reviewed articles were conducted by using literature review approach in which ten selected articles published from 2016 to 2021 at reputable international journals to be reviewed comprehensively. The selected articles were explored at different learning atmospheres to find out metacognitive strategies use and its direct impact on listening comprehension. The reviewed results were discussed in detail based on various findings of metacognitive strategies components (problem-solving, person knowledge, mental translation, planning and evaluation and directed attention) that highly used by language learners and also its impact during learning listening. In conclusion, metacognitive strategies use on listening comprehension has contributed crucially for L2 and EFL learners to regulate, direct, monitor, and control their cognitive ability during language learning process and this self-regulation based learning has influenced listening learning outcome.